VEGF(165) promotes the osteolytic bone destruction of Ewing's sarcoma tumors by upregulating RANKL - Guan, Hui (2009)
The purpose of this study was to determine whether vascular endothelial growth factor-165 (VEGF(165)) contributed to the osteolytic process in Ewing's sarcoma. VEGF(165) induced osteoclast formation from murine bone marrow cells. Tartrate-resistant acid phosphatase (TRAP) staining demonstrated significantly fewer osteoclasts in VEGF-inhibited TC/siVEGF(7-1) tumors compared to TC71 parental or TC/si-control tumors. Receptor activator NF-κB (RANKL), a critical osteoclastogenic factor, was decreased in TC/siVEGF(7-1) cells. Incubation of these cells with recombinant VEGF(165) upregulated RANKL in a dose and time-dependent manner. The induction of (RANKL) by VEGF(165) was also demonstrated in MC3T3-E1 mouse osteoblast cells and bone marrow stromal cells. This upregulation was transcriptionally mediated by an effect on the RANKL promoter. Both VEGF and EWS/FLI-1 increased RANKL promoter activity. Taken together, these data suggest that modulation of RANKL by VEGF(165) may be one of the mechanisms responsible for the osteolytic process induced by Ewing's sarcoma cells. VEGF(165) may, therefore, play an important role in modulating RANKL gene expression in the bone marrow microenvironment during the metastatic process, thereby contribution to tumor induced bone lysis.